Assessing soil erosion after fire and rehabilitation treatments in NW Spain: performance of rusle and revised Morgan-Morgan-Finney models - Fernández, C. (2020)
Although the Revised Universal Soil Loss Equation (RUSLE) and the revised Morgan–Morgan–Finney (MMF) are well‐known models, not much information is available as regards their suitability in predicting post‐fire soil erosion in forest soils. The lack of information is even more pronounced as regards post‐fire rehabilitation treatments. This study compared the soil erosion predicted by the RUSLE and the revised MMF model with the observed values of soil losses, for the first year following fire, in two burned areas in NW of Spain with different levels of fire severity. The applicability of both models to estimate soil losses after three rehabilitation treatments applied in a severely burned area was also tested. The MMF model presented reasonable accuracy in the predictions while the RUSLE clearly overestimated the observed erosion rates. When the R and C factors obtained by the RUSLE formulation were multiplied by 0·7 and 0.865, respectively, the efficiency of the equation improved. Both models showed their capability to be used as operational tools to help managers to determine action priorities in areas of high risk of degradation by erosion after fire.